2016
DOI: 10.1002/chem.201600927
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Swarming: Depending on Concentration, an Amphiphilic Ruthenium Polypyridyl Complex Induces Cell Death via Two Different Mechanisms

Abstract: The crystal structure and in vitro cytotoxicity of the amphiphilic ruthenium complex [3](PF6)2 are reported. Complex [3](PF6)2 contains a Ru−S bond that is stable in the dark in cell‐growing medium, but is photosensitive. Upon blue‐light irradiation, complex [3](PF6)2 releases the cholesterol–thioether ligand 2 and an aqua ruthenium complex [1](PF6)2. Although ligand 2 and complex [1](PF6)2 are by themselves not cytotoxic, complex [3](PF6)2 was unexpectedly found to be as cytotoxic as cisplatin in the dark, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 66 publications
5
25
1
Order By: Relevance
“…The ligand photosubstitution was characterized by clear isosbestic points in the UV/Vis spectra (450 to 476 nm depending on the compound), as shown in Figure . For each of these reactions a bathochromic shift of the 1 MLCT band was observed, which is consistent with earlier reports on the formation of monoaqua‐ruthenium complexes in aqueous solution . Most complexes have a photosubstitution quantum yield ( Φ 450 ) of 0.5–2 percent, leading to photosubstitution reactivities ( ξ =Φ 450 < mx> ϵ 450, in which ϵ 450 is the molar absorption at 450 nm) on the order of ten to hundreds ( ξ =11–256).…”
Section: Resultssupporting
confidence: 89%
“…The ligand photosubstitution was characterized by clear isosbestic points in the UV/Vis spectra (450 to 476 nm depending on the compound), as shown in Figure . For each of these reactions a bathochromic shift of the 1 MLCT band was observed, which is consistent with earlier reports on the formation of monoaqua‐ruthenium complexes in aqueous solution . Most complexes have a photosubstitution quantum yield ( Φ 450 ) of 0.5–2 percent, leading to photosubstitution reactivities ( ξ =Φ 450 < mx> ϵ 450, in which ϵ 450 is the molar absorption at 450 nm) on the order of ten to hundreds ( ξ =11–256).…”
Section: Resultssupporting
confidence: 89%
“…Recently, the same group designed a photosensitive Ru(II) complex 14e . 245 The complex was found to have similar cytotoxicity as cisplatin in the dark and increased photocytoxicity after 24 h incubation with blue light activation. Interestingly, the complex had monomer characteristics at a low concentration (< 3.5 μM) and it released the monodentate ligand under blue light activation.…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 94%
“…We reported earlier on a method to cleave methionine‐ and biotin‐based ligands from a ruthenium(II) polypyridyl complex using visible light . Following the steps of Lo et al, Ward et al, and others, who showed that biotin‐tagged metal compounds could keep the biotin affinity for (strept)avidin, we embarked on investigating synthetically useful methods to functionalize photosubstitutionally active ruthenium polypyridyl complexes such as [Ru(tpy)(bpy)(Cl)]Cl with a free biotin fragment that can be removed by visible light, for future use in photochemotherapy , …”
Section: Introductionmentioning
confidence: 99%